2022
DOI: 10.15832/ankutbd.714568
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the Application of Foliar Jasmonic Acid and Drought Stress on Grain Yield and Some Physiological and Biochemical Characteristics of Chenopodium quinoa Cultivars

Abstract: Water shortage is a critical problem touching plant growth and yield in arid and semi-arid areas such as Iran. Plant hormones such as jasmonic acid (JA) play a crucial role in altering plant morphology in response to stress. To investigate the effect of JA and drought stress on grain yield and some physiological and biochemical characteristics of quinoa cultivars, a split-plot factorial experiment based on randomized complete block design with three replications was conducted at Kerman Agricultural and Natural… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…In Burkina Faso, application of 100 kg N ha -1 increased quinoa grain yield by 37%, reaching 1380 kg ha -1 (Abdolahpour et al, 2021). In Iran, 100 kg N ha -1 seemed to be the optimal N rate producing 2790 kg ha -1 (Keshtkar et al, 2022). Under arid conditions in Syria, N fertilization at 90 kg N ha -1 resulted in the highest grain yield (5320 kg ha -1 ) whereas higher N rates decreased quinoa grain yield.…”
Section: Nitrogen Fertilizationmentioning
confidence: 96%
“…In Burkina Faso, application of 100 kg N ha -1 increased quinoa grain yield by 37%, reaching 1380 kg ha -1 (Abdolahpour et al, 2021). In Iran, 100 kg N ha -1 seemed to be the optimal N rate producing 2790 kg ha -1 (Keshtkar et al, 2022). Under arid conditions in Syria, N fertilization at 90 kg N ha -1 resulted in the highest grain yield (5320 kg ha -1 ) whereas higher N rates decreased quinoa grain yield.…”
Section: Nitrogen Fertilizationmentioning
confidence: 96%
“…In addition, exogenous application of polyamines on mung bean also increased the photosynthetic rate and induced the accumulation of osmoprotectants, improving its tolerance to water deficits (Sadeghipour, 2019). Foliar sprays of jasmonic acid on quinoa were found to increase yield by 16% compared to controls under water-deficit conditions (Keshtkar et al, 2022). Canales et al (2019) found that salicylic acid can interact with polyamines in a complex way to build a signaling network that mitigates the adverse effects of water deficiency on oats (Gong et al, 2022).…”
Section: Proper Management Practices In Field Cultivationmentioning
confidence: 99%